En beskeden fejring? Reformationsjubilæet 1917 - Bach-Nielsen, Carsten (Kirkehistoriske Samlinger, 2011)
Summary A modest celebration? The fourth Reformation centenary 1917 The Reformation was celebrated at its fourth centenary in Denmark 1917, but in a somewhat subdued tone caused by the World War. Denmark should bear in mind that the end of war would probably result in a plebiscite in German occupied Schleswig. Danish authorities should avoid provoking the German Empire. On the other hand Denmark should not appear too cordial in its attitude to Germany because of the two countries’ shared Lutheran confession. The celebration was prepared by the Ministry of Ecclesiastical Matters and actually gained some interest; undoubtedly due to the rather uneventful and isolated life of a neutral nation. Contacts were made with Norwegian and Swedish churches. As the German Emperor abandoned the celebrations amongst the Lutheran churches within his empire, Danish public seems to have become more secure that a Danish celebration would actually be seen as a celebration of Lutheranism, not as a tribute to German nationalism. The celebration was official with services attended by the Royal House in Copenhagen, with an official day off for all pupils – and with quite a number of publications. The fourth centenary was to be an opportunity to rethink Lutheranism. The German »Kulturprotestantismus« was singing its swan song in the slaughterhouses of Flanders while a new generation was looking forward to a more existentialist interpretation of Luther’s message. Now the history of the reformation was superseded by a new interest in the essentials of Christianity in a world without worth in itself.